RANCANG BANGUN SISTEM INFORMASI PRESENSI KARYAWAN BERBASIS WEB PADA TOKO KUE SUMBER MAS JAKARTA - Nasril Nasril; Dandi (POLITEKNIK LP3I JAKARTA, 2023)
The role of information technology in every information process is very important in processing data into accurate information according to user needs. Toko Kue Sumber Mas Jakarta is a shop that sells cakes. This shop has a fairly large business premises, so there are many employees working there. The problem addressed in this practicum is how to design and create an effective and efficient attendance information system at Sumber Mas Jakarta Cake Shop. The discussion is limited to handling several processes, starting from the attendance process for each employee to exporting employee attendance reports. However, to overcome these problems, several steps are required, namely analyzing the system through interviews, with the aim of obtaining information about the employee attendance mechanism, then designing the system, including Use Case Diagram, Scenario Diagram, Activity Diagram, Sequence Diagram, Class Diagram, Database Normalization, File Classification, ERD, LRS, and User Interface. Next, implement the system and discuss the results of the system implementation.